Presence of Ehrlichia sp and Hepatozoon sp in dogs infested with ticks or with previous exposure attended at a veterinary centre in Trujillo, Peru - Alva Díaz, Katherine (2024)
The present study determined the prevalence of Ehrlichia sp morulae and Hepatozoon sp gamonts in dogs treated at a veterinary medical centre in the city of Trujillo. Blood samples were taken from dogs infested with ticks or exposed in the three months prior to the study. Blood samples (3 mL) were collected from the cephalic vein of 95 dogs in EDTA tubes. The samples were centrifuged. A drop of the phlogistic layer of each sample was placed on a slide, which was extended with a coverslip and subjected to Wright staining. The smears were observed under an optical microscope at 40X and 100X. A prevalence of Ehrlichia sp of 31.6 ± 9.4% was found. No presence of Hepatozoon sp gamonts was observed.